81.8k views
0 votes
Do you know how to do this?

Do you know how to do this?-example-1
User Arsibalt
by
6.0k points

1 Answer

0 votes

Answer:


y=4(3)^(x)

Explanation:

Let the exponential function is,

f(x) = (b)ˣ

If this function has the base (b) = 3, function will be.

f(x) = (3)ˣ

If this function is transformed by a vertical stretch by a factor of 4,

New function will be,

g(x) = 4(3)ˣ

If the function 'g' is reflected across y-axis, new function will be,

h(x) = g(-x)

h(x) =
4(3)^(x)

Therefore, equation of the function will be,


y=4(3)^(x)

User Djunehor
by
5.1k points